New carnivoraforms from the latest Paleocene of Europe and their bearing on the origin and radiation of Carnivoraformes (Carnivoramorpha, Mammalia). Issue 2 (3rd March 2016) - Solé, Floréal; Smith, Thierry; De Bast, Eric; Codrea, Vlad; Gheerbrant, Emmanuel
ABSTRACT: We report the discovery of the earliest European carnivoraforms, based on two new taxa from the latest Paleocene of France and Romania. A new species of Vassacyon, V. prieuri, from the locality of Rivecourt (MP6b; Oise, France) (MP = Mammalian Paleogene reference levels) is described based on a dentary fragment and isolated teeth. This species displays several primitive features compared with species of Vassacyon known from the early Eocene of North America and Europe. A second Paleocene carnivoraform, cf. Gracilocyon sp., is described based on fragmentary specimens from the locality of Jibou (MP6b; Transylvania, Romania). Carnivoraformes were previously unknown in Europe before the Eocene, and Vassacyon prieuri and cf. Gracilocyon sp. are their oldest records in Europe. These discoveries favor the hypothesis of a dispersal of these two genera from Europe to North America during the Paleocene-Eocene Thermal Maximum. Vassacyon prieuri and cf. Gracilocyon sp. strengthen support for the level MP6b and its correlation with the Clarkforkian. The geographic origin of the Carnivoraformes remains unknown. However, based on the observed biochronological and geographic distributions of the carnivoraforms, we infer a possible Asian origin for this group. In this scenario, Gracilocyon and Vassacyon dispersed to Europe during the Clarkforkian MP6b time, probably together with rodent taxa, whereas Uintacyon dispersed from Asia to North America shortly after rodents and tillodonts. http://zoobank.org/urn:lsid:zoobank.org:pub:FC885E7F-877A-4454-9902-DF118B8C8693 SUPPLEMENTAL DATA—Supplemental materials are available forthis article for free atwww.tandfonline.com/UJVP Citation for this article: Solé, F., T. Smith, E. de Bast, V. Codrea, and E. Gheerbrant. 2016. New carnivoraforms from the latest Paleocene of Europe and their bearing on the origin and radiation of Carnivoraformes (Carnivoramorpha, Mammalia). Journal of Vertebrate Paleontology. DOI: 10.1080/02724634.2016.1082480.